2004
DOI: 10.1097/00006676-200405000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Complications of Pancreas Transplantation

Abstract: Early diagnosis of vascular complications after pancreas transplantation is of paramount importance for the appropriate treatment with organ salvage. Based on our experience, we suggest that VT can be effectively treated with anticoagulation. Aspirin is sufficient for PSVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 39 publications
0
10
0
2
Order By: Relevance
“…managed partial venous thrombosis (n = 10) with aspirin alone and showed no progression of thrombosis. They reported recanalization of the thrombosed veins on follow‐up imaging and, overall, there was no effect on graft survival 32. Our retrospective review of images at 3 months and subsequently showed that majority of patients who were not anticoagulated for thrombosis had a reduction in grade of thrombosis to no thrombosis or lower grade thrombosis.…”
Section: Discussionmentioning
confidence: 72%
“…managed partial venous thrombosis (n = 10) with aspirin alone and showed no progression of thrombosis. They reported recanalization of the thrombosed veins on follow‐up imaging and, overall, there was no effect on graft survival 32. Our retrospective review of images at 3 months and subsequently showed that majority of patients who were not anticoagulated for thrombosis had a reduction in grade of thrombosis to no thrombosis or lower grade thrombosis.…”
Section: Discussionmentioning
confidence: 72%
“…Las complicaciones más frecuentes que conllevan al fracaso del injerto son de causa inmunológica, como el rechazo agudo (7 a 25%) y crónico (2 a 33%), y de causa técnica (trombosis, pancreatitis, sangrado, dehiscencia de anastomosis duodenal, pseudoaneurismas, fístula pancreática), actualmente en menos del 8% (27,(43)(44)(45)(46)(47) . Las complicaciones más frecuentes son la trombosis y el rechazo agudo, siendo las dos causas principales de pérdida del injerto (48) .…”
Section: Discussionunclassified
“…En este primer caso, se produjeron, como hemos documentado, complicaciones que fueron de impacto leve (pancreatitis leve, fístula controlada y autolimitada, y trombosis de la arteria esplénica, compensada por el suministro de colaterales de la arteria mesentérica superior), no requiriendo de reoperaciones ni readmisiones hospitalarias. El páncreas es uno de los órganos más propensos a la trombosis después del trasplante, debido al bajo flujo sanguíneo a nivel parenquimal, el cual disminuye aún más al extirpar el bazo, y al invariable edema del órgano por injuria por isquemia-reperfusión y manipulación durante las fases de extracción y trabajo de banco (46,47,51) . La trombosis es principalmente venosa, se produce precozmente en los primeros días post-trasplante, y habitualmente obliga a la extirpación del injerto.…”
Section: Discussionunclassified
“…The ramifications of venous thrombosis are more problematic in the pancreas transplant patient given the risk of developing post‐thrombotic syndrome in addition to potential allograft dysfunction or loss. Treatment of this problem in this population continues to consist of standard anticoagulation and/or operative thrombectomy, although the latter can be associated with significant peri‐operative risks (11–13). Despite its success in non‐transplant patients, little has been reported on the efficacy of catheter‐directed therapy for venous thromboses in pancreas transplant recipients.…”
Section: Discussionmentioning
confidence: 99%